Long-Term Suppression of Circulating Proinflammatory Cytokines in Multiple Sclerosis Patients Following Autologous Haematopoietic Stem Cell Transplantation - Hendrawan, Kevin; Khoo, Melissa L. M.; Visweswaran, Malini; Massey, Jennifer C.; Withers, Barbara; Sutton, Ian; Ma, David D. F.; Moore, John J. (Frontiers in Immunology, 2022)
Autologous haematopoietic stem cell transplantation (AHSCT) is a therapeutic option for haematological malignancies, such as non-Hodgkin’s lymphoma (NHL), and more recently, for autoimmune diseases, such as treatment-refractory multiple sclerosis (MS). The immunological mechanisms underlying remission in MS patients following AHSCT likely involve an anti-inflammatory shift in the milieu of circulating cytokines. We hypothesised that immunological tolerance in MS patients post-AHSCT is reflected by an increase in anti-inflammatory cytokines and a suppression of proinflammatory cytokines in the patient blood. We investigated this hypothesis using a multiplex-ELISA assay to compare the concentrations of secreted cytokine in the peripheral blood of MS patients and NHL patients undergoing AHSCT. In MS patients, we detected significant reductions in proinflammatory T helper (Th)17 cytokines interleukin (IL)-17, IL-23, IL-1β, and IL-21, and Th1 cytokines interferon (IFN)γ and IL-12p70 in MS patients from day 8 to 24 months post-AHSCT. These changes were not observed in the NHL patients despite similar pre-conditioning treatment for AHSCT. Some proinflammatory cytokines show similar trends in both cohorts, such as IL-8 and tumour necrosis factor (TNF)-α, indicating a probable treatment-related AHSCT response. Anti-inflammatory cytokines (IL-10, IL-4, and IL-2) were only transiently reduced post-AHSCT, with only IL-10 exhibiting a significant surge at day 14 post-AHSCT. MS patients that relapsed post-AHSCT exhibited significantly elevated levels of IL-17 at 12 months post-AHSCT, unlike non-relapse patients which displayed sustained suppression of Th17 cytokines at all post-AHSCT timepoints up to 24 months. These findings suggest that suppression of Th17 cytokines is essential for the induction of long-term remission in MS patients following AHSCT.